IMPLEMENTASI PROGRAM REHABILITASI RUMAH TIDAK LAYAK HUNI DI KABUPATEN MAGETAN TAHUN 2014 - Nastiti, Lawuning; Adhi, Suwanto; Herawati, Nunik Retno (Journal of Politic and Government Studies, 2016)
Unhabitable House Rehabilitation Program is a Program who initiated by Magetan District Government for low income earners to occupy the habitable house. Implementation of Unhabitable House Rehabilitation Program in Magetan Regency in its practice had run well enough because the implementation in most of villages succeeded to repair some house components such as roof, floor, wall, and toilet which in the begining seemed to be unhabitable house became habitable house. However, there were still villages that had been found in this program’s implementation could repair only one house damage component, so that other components had not been handled yet. Obstacles of this program was inequality of budget distribution in each village because the rule in Regent Law No. 44 of 2014 did not write maximum limit of assistance for each village, so that for village which had a large number of house rehabilitation implementation, budget that had to be given out also more decreased. If budget was less so the component which was repaired were less too, so that aim rettainment for habitable house had not utterly reached yet. Recommended suggestions from the researcher was assistance for each village should be appropriate with total poor people in each village, also government should make maximum limit for program receiver in each village in order to the budget revenue was more equally.